Low Rate of SARS-CoV-2 Infections in Symptomatic Patients Attending a Pediatric Emergency Department - Zurl, Christoph; Eber, Ernst; Siegl, Anna; Loeffler, Sabine; Stelzl, Evelyn; Kessler, Harald H.; Egger, Markus; Schweintzger, Nina A.; Zenz, Werner; Strenger, Volker (Frontiers in Pediatrics, 2021)
Children and adolescents seem to be at lower risk of developing clinical symptoms of COVID-19. We analyzed the rate of SARS-CoV-2 infections among 3,605 symptomatic children and adolescents at 4,402 outpatient visits presenting to a pediatric emergency department. In a total of 1,105 (32.6%) episodes, the patients fulfilled clinical case definitions for SARS-CoV-2 infection and were tested by nucleic acid testing. A SARS-CoV-2 infection was diagnosed in 10/1,100 episodes (0.3% of analyzed episodes, 0.91% of validly tested patients). Symptoms at presentation did not differ between patients with and without SARS-CoV-2 infection, apart from the frequency of measured temperature ≥37.5°C at presentation. Three percent of analyzed children reported disturbances of olfactory or gustatory senses, but none of them was infected with SARS-CoV-2. The rate of SARS-CoV-2 infections among symptomatic children and adolescents was low and SARS-CoV-2 infections could not reliably be differentiated from other infections without nucleic acid testing.